Analisis Perbandingan Kinerja Keuangan Pemerintah Daerah Terhadap Dampaknya Pertumbuhan Ekonomi Kabupaten/Kota di Indonesia pada Tahun 2019-2023 - Nur’ain Rohmatia Nusi; Herwin Mopangga; Rifi Fazrina Djuuna (Economic Reviews Journal, 2025)
This research aims to analyze the effect of local government financial performance on economic growth in regencies/cities in Indonesian during the 2019-2023 period. This research uses a quantitative approach with secondary data sourced from the Directorate General Of Finance (DJPK) and the Central Statistics Agency (BPS). This research focuses on regional financial achievments such as the Regional Financial Independence Ratio (RKKD), Revenue Sharing Fund (DBH), General Allocation Fund (DAU), Special Allocation Fund (DAK), and Ratio of the Degree of Fiscal Desentralization (RDDF) in influencing the rate of economic growth. The observation include 481 regencies/cities for five years with andom Effect Model (REM) model and generalized least squares (GLS) solution model. The results of thi research indicate that the Regional Financial Independence Ratio (RKKD) and Revenue Sharing Fund (DBH) have a significant effect that can reduce economic growth, which is a sign that the increase in regional fical capacity has not been accompanied bye effective budget management. In contrast, the ratio of the Degree of Fiscal Decentralization (RDDF) has a positive and significant effect, indicating that regions that able to increase their own source revenue (PAD) are relatively more likely to encourage economic growth. Meanwhile, DAU and DAK do no show a significant effect on economic growth.